REVIEW TRICKLE IRRIGATION APPLICATION IN GROUNDWATER IRRIGATION SCHEMES - Prastowo .; S. Hardjoamidjojo; Bambang Pramudya; K. Murtilaksono (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT The Government of Indonesia has developed groundwater irrigation schemes in some province e.g. East Java, Central Java, Yogyakarta, Wast Java, Bali, West Nusa Tenggara and East Nusa Tenggara. However, not all regions were able to optimally utilize it. The irrigation effeciency of groundwater irrigation scheme was about 59%, whe;; the wells-pumping efficiencies were varied from 28 to 98 %. In thefuture, the irrigation effieciency should be increased to anticipate water deficit during dry season. The application of trickle irrigation in indonesia has not been widely developed. Although trickle system has been used, however, it is still limited for few commercial agribusinesses. Trickle irrigation systems have a prospect to be developed in some regions having limited water resources. For preliminary stage, the systems could be applied in groundwater irrigation schemes that have been developed either by farmers or government. Keywords: irrigation effieciency, trickle irrigation, groundwater irrigation schemes